Calibração do Sistema de Aquisição de Informação 3D do LOME - Maria Cândida Felgueiras Seabra Pinto Coelho (2004)
The main goal of the present report is to briefly describe the steps that had been followed to calibrate the three-dimensional (3D) information acquisition system being developed in the Optical and Experimental Mechanics Laboratory (LOME). Thus, this report is composed by four sections: in the first one, a introduction to the LOME's acquisition system is presented; in the second, the setup used to calibrate that system is described; in the third, the values, supplied from the manufacturers, of some intrinsic parameters of the camera and of projector are indicated; and in the fourth and last section, all the estimated calibration parameters are presented.